ERP and information systems : integration or disintegration - Samara, Tarek (London : ISTE, 2015)
Annotation This research attempts to explore and identify eventual relationships between the evolution of ERP systems and information systems integration or disintegration. The aim of this research is to know if the relationships between the ERP systems and the information systems are guided by certain factors and, as a result, to understand, more in-depth, the factors affecting these relationships. More precisely, this analysis aims to study whether assigned values given to these factors could guide the evolution of ERP systems in a manner that promotes IS integration; and if the opposite assigned values to these same factors could guide the evolution of ERP systems in a manner that provokes IS disintegration instead.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 13, 2015).
Keywords: Business -- Data processing; Engineering -- Data processing; Computer networks; Information technology; Internet; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; Business -- Data processing; Computer networks; Engineering -- Data processing; Information technology; Internet; Electronic books